Time-resolved momentum microscopy with fs-XUV photons at high repetition rates with flexible energy and time resolution - Karl Jakob Schiller; Lasse Sternemann; Matija Stupar; Alan Omar; Martin Hoffmann; Jonah Elias Nitschke; Valentin Mischke; David Maximilian Janas; Stefano Ponzoni; Giovanni Zamborlini; Clara Jody Saraceno; Mirko Cinchetti (Scientific Reports)
Abstract Time-resolved momentum microscopy is an emerging technique based on photoelectron spectroscopy for characterizing ultrafast electron dynamics and the out-of-equilibrium electronic structure of materials in the entire Brillouin zone with high efficiency. In this article, we introduce a setup for time-resolved momentum microscopy based on an energy-filtered momentum microscope coupled to a custom-made high-harmonic generation photon source driven by a multi-100 kHz commercial Yb-ultrafast laser that delivers fs pulses in the extreme ultraviolet range. The laser setup includes a nonlinear pulse compression stage employing spectral broadening in a Herriott-type bulk-based multi-pass cell. This element allows flexible tuning of the driving pulse duration, providing a versatile time-resolved momentum microscopy setup featuring two operational modes designed to enhance either the energy or time resolution. We show the capabilities of the system by tracing ultrafast electron dynamics in the conduction band valleys of a bulk crystal of the 2D semiconductor WS2. Using uncompressed driving laser pulses, we demonstrate an energy resolution better than (107 ± 2) meV, while compressed pulses lead to a time resolution better than (48.8 ± 17) fs.